Золотая роза - Паустовский Константин Георгиевич (Серия "Внеклассное чтение", 2008)
Экземпляры: С/а ДБ (20091210) / Инвентарный номер: 95661 / Цена: 149.27 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: П 21 / ББК: 84(2Рос=Рус)6